2009
DOI: 10.1089/scd.2009.0003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Implications of CD34 Expression in Human Adipose–Derived Stem/Progenitor Cells

Abstract: CD34 is frequently used as a marker of adipose-derived stem/stromal/progenitor cells (ASCs). However, CD34 expression in human ASCs (hASCs) decreases over time in culture, and the implications of this remain unclear. In this study, we sorted shortly-cultured hASCs into CD34+ and CD34- fractions and compared their biological functions. Results indicated that CD34+ hASCs were more proliferative and had a greater ability to form colonies. In contrast, CD34- cells showed a greater ability for differentiation into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
161
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(190 citation statements)
references
References 39 publications
21
161
2
6
Order By: Relevance
“…The CD34-positive cells in SVF are localized in the blood vessels in adipose tissue, and their staining is different from that of CD31 in that CD34-positive cells are visible in the adventitia of all blood vessels (16). Some data indicate that CD34-positive SVF cells have a higher proliferation rate than the CD34-negative cells (27). Another study showed that the CD34-positive cell population from cultured SVF (but not CD34-negative cells) was able to produce lipid-droplet formation activity under adipogenic culture conditions (18).…”
Section: Discussionmentioning
confidence: 99%
“…The CD34-positive cells in SVF are localized in the blood vessels in adipose tissue, and their staining is different from that of CD31 in that CD34-positive cells are visible in the adventitia of all blood vessels (16). Some data indicate that CD34-positive SVF cells have a higher proliferation rate than the CD34-negative cells (27). Another study showed that the CD34-positive cell population from cultured SVF (but not CD34-negative cells) was able to produce lipid-droplet formation activity under adipogenic culture conditions (18).…”
Section: Discussionmentioning
confidence: 99%
“…Although generally considered to be a marker of haematopoietic progenitor cells, it is now agreed that there is positive CD34 expression on a subset of freshly isolated ASCs. 44,45 It has been reported that ASCs lose the expression of CD34 within 3 passages in tissue culture. This tissue culture phenomenon, has been largely unrecognized until recently.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the use of surface markers has been pivotal to recent progress in localizing ASCs within WAT. other studies ( 22,49,123,124 ). Pericytes thereby isolated using fl uorescence-activated cell sorting (FACS) were found to be multipotent, even after long-term passaging in culture, and to express MSC markers such as CD44, CD73, CD90, and CD105 ( Table 1 ) ( 121 ).…”
Section: Beauty Is Only Skin Deep: Cell Surface Markers In Asc Characmentioning
confidence: 97%
“…between different functional subgroups of ASCs, especially with regard to adipogenesis: although CD34-SVCs can undergo adipogenesis ( 47,121,123 ), CD34+ cells make up approximately 82% of the SVF ( 106 ) and are consistently more adipogenic in vitro than CD34-populations after negative selection for CD31 ( 124,161,189 ). Similarly, exclusion of CD34+ cells in muscle regeneration studies inhibits ectopic adipose formation both in vitro and in vivo ( 190 ), indicating that CD34-cells are incapable of adipogenesis.…”
Section: Ectodermal Cellsmentioning
confidence: 99%